Circulating inflammatory cytokines alter transcriptional activity within fibrotic tissue of Dupuytren's disease patients. Issue 3 (11th May 2021) - Wang, Mark L.; Rajpar, Ibtesam; Ruggiero, Nicholas A.; Fertala, Jolanta; Steplewski, Andrzej; Beredjiklian, Pedro K.; Rivlin, Michael R.; Chen, Yong; Feldman, George J.; Fertala, Andrzej; Tomlinson, Ryan E.
Abstract: Dupuytren's disease is a benign fibroproliferative disorder of the hand that results in disabling digital contractures that impair function and diminish the quality of life. The incidence of this disease has been correlated with chronic inflammatory states, but any direct association between inflammatory cytokines and Dupuytren's disease is not known. We hypothesized that advanced fibroproliferation is associated with increased levels of circulating inflammatory cytokines. Blood and fibrotic cord tissue were collected preoperatively from patients with severe contracture and control patients. Blood plasma concentrations of known inflammatory cytokines were evaluated using a multiplex immunoassay. Proteins from the cord tissue were analyzed by RNA sequencing and immunohistochemistry. Moreover, collagen‐rich cords were analyzed using Fourier‐transform infrared spectroscopy. The results indicate that patients exhibited significantly elevated circulating inflammatory cytokines, including tumor necrosis factor‐α (TNF‐α), interleukin (IL)‐2, and IL‐12p70, as compared with controls. Similarly, IL‐4 and IL‐13 were detected significantly more frequently in Dupuytren's disease as compared with control. RNA sequencing revealed 5311 differentially expressed genes and distinct clustering between diseased and control samples. In addition to increased expression of genes associated with fibroproliferation, we also observed upregulation of transcripts activated by inflammatory cytokines, including prolactin inducible protein and keratin intermediate filaments. IL‐2, but not TNF‐α, was detected in fibrotic cord tissue by immunohistochemistry. Finally, spectroscopic assays revealed a significant reduction of the collagen content and alterations of collagen cross‐linking within the Dupuytren's disease tissues. In total, our results illustrate that patients with severe Dupuytren's disease exhibit substantially elevated circulating inflammatory cytokines that may drive fibroproliferation. Clinical Significance: The results from this study establish the basis for a specific cytokine profile that may be useful for diagnostic testing and therapeutic intervention in Dupuytren's disease.